2007
DOI: 10.1071/sh07033
|View full text |Cite
|
Sign up to set email alerts
|

General practice intervention to increase opportunistic screening for chlamydia

Abstract: We describe an 18-month intervention that was designed to improve opportunistic screening for chlamydia in General Practice. Key strategies included engaging and informing general practitioners, adopting a simplified screening protocol, providing feedback on practice testing performance and developing resources for use with patients. This uncontrolled before and after study found that the overall impact on testing was modest and largely transient, and was insufficient to impact on the current chlamydia epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 6 publications
0
41
0
Order By: Relevance
“…The lower rates of testing within GPs and ACCHSs compared with SHSs could be due to a number of factors: patients declining testing; patients not being offered testing (staff lacking awareness of screening guidelines, due lack of time and awareness about chlamydia testing amongst clinic staff, or sensitivities regarding sexual health issues); or other clinical priorities [24-26]. In order to achieve higher chlamydia testing rates in GP and ACCHS settings, supportive quality improvement strategies are warranted [27,28] as well as initiatives such as offering a test to all patients prior to the consultation [29] Quality improvement audits are a key feature of the Closing the Gap funding initiatives particularly involving ACCHSs [30] but do not currently explore STI testing patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The lower rates of testing within GPs and ACCHSs compared with SHSs could be due to a number of factors: patients declining testing; patients not being offered testing (staff lacking awareness of screening guidelines, due lack of time and awareness about chlamydia testing amongst clinic staff, or sensitivities regarding sexual health issues); or other clinical priorities [24-26]. In order to achieve higher chlamydia testing rates in GP and ACCHS settings, supportive quality improvement strategies are warranted [27,28] as well as initiatives such as offering a test to all patients prior to the consultation [29] Quality improvement audits are a key feature of the Closing the Gap funding initiatives particularly involving ACCHSs [30] but do not currently explore STI testing patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 7% of attendees were tested within a 12-month period compared with 25% and 40% retested by 4 and 12 months of a positive test, respectively. This may reflect annual testing being largely opportunistic in GP clinics24 and subject to numerous barriers—particularly time constraints and when unrelated to the presenting complaint 25. In contrast, retesting is more likely to be done in the context of a sexual health consultation and after the individual is established at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling data has shown that testing rates need to be increased to 30% or more in order to reduce the prevalence of chlamydia [8]. Barriers to testing by GPs include lack of time, discomfort with sexual health issues [9] and lack of knowledge about the benefits of chlamydia screening [10]. …”
Section: Introductionmentioning
confidence: 99%